La communauté juive de Djerba - Sellamy, Jean-Claude (L'Arche, 1972)
Keywords: Judaïsme – Djerba

Les Juifs de Djerba: les témoins de la Bible - Cohen, Alain; Coursez, Robert; Nizan, Georges (CNRS-SFP, 1977)
Ce documentaire constitue un témoignage sur la survivance de la communauté juive de l'île de Djerba en Tunisie, implantée depuis la destruction du Temple de Jérusalem en 586 avant J.C.
Keywords: Judaïsme – Djerba

Jews under Muslim Rule in the late Nineteenth Century - Littman, David (The Wiener Library Bulletin, 1975)
1864 : The looting of Jewish Quarters on the Island of Djerba by Akara and Ouerghemma
Keywords: Judaïsme – Djerba

Analysis of Genetic Data on Jewish Populations I. Historical Background, Demographic Features, and Genetic Markers - Bonne-Tamir, Batsheva; Karlin, Samuel; Kenett, Ron (American Journal of Human Genetics, 1979)
Part I describes the data sets on which the analysis of Part II is based. This covers the nature of the populations sampled, the extent to which the samples are representative, and a brief review of historical and demographic facts on the populations involved.
Keywords: Judaïsme – Djerba

Les sages de Tunis et de Djerba: récits de la vie merveilleuse des grands sages et luminaires de la nation juive, qui ont vécu à Tunis et Djerba - Katsenellebogen, G. (Yéshiva "Hod Yoseph", 1973)
Keywords: Judaïsme – Djerba

Retour de Tunisie - Maurice, Jack (Information Juive, 1977)
Keywords: Judaïsme – Djerba

Exhibition on Arab Jews - Friedman, Keren Tzionah; Valensi, Lucette (1977)
The Judah L. Magnes Museum
Keywords: Judaïsme – Djerba

Towards a Description of the Traditional Pronunciation of the Jewish Community of Djerba - Katz, Ktzia (Proceedings of the World Congress of Jewish Studies / דברי הקונגרס העולמי למדעי היהדות, 1973)
Keywords: Judaïsme – Djerba

Deux rapports de Salomon Reinach sur les Juifs de Tunisie au début du protectorat - Attal, Robert (Revue des études juives, 1979)
Keywords: Judaïsme – Djerba

The jews of Arab lands: a history and source book - Stillman, Norman A. (The jewish publication society, 1979)
Keywords: Judaïsme – Djerba

Femmes et voisinages à Hara Kebira : rapport d’un stage effectué à Hara Kebira, dans l’île de Jerba - Reenen, Joke van (V. U., 1979)
Keywords: Judaïsme – Djerba

The Reading Tradition of the Bible and the Mishna in the Community of Djerba (Tunis) - Ktsia, Kats (The Hebrew University of Jerusalem, 1970)
Keywords: Judaïsme – Djerba

Ethnic Boundaries and Cultural Paradigms: The Case of Southern Tunisian Immigrants in Israel - Deshen, Shlomo (Ethos, 1976)
Keywords: Judaïsme – Djerba

Hebrew language tradition of the Community of Djerba (Tunisia) - Katz, Ktzia (ha-Universitah ha-ʻIvrit be-Yerushalayim, ha-Makhon le-madaʻe ha-Yahadut, Mifʻal Masorot ha-lashon shel edot Yiśraʼel, 1977)
Keywords: Judaïsme – Djerba

Femmes et voisinages à Hara Kebira : rapport d'un stage effectué à Hara Kebira, dans l'île de Jerba - Joke van Reenen, Johanna Hendrika (Université Libre, 1979)
Keywords: Judaïsme – Djerba

Gesänge der Juden auf der Insel Djerba - Lachmann, Robert (Magnes Press, Hebrew University, 1978)
Keywords: Judaïsme – Djerba

Culture and Politics in a Village of Immigrants from Djerba - Deshen, Shlomo; Jaeger, D. (Rural Settlements of New Immigrants in Israel, 1971)
Keywords: Judaïsme – Djerba

Robert Lachmann: his Achievement and his Legacy - Gerson-Kiwi, Edith (Yuval, 1974)
Keywords: Judaïsme – Djerba

Ritualization of literacy: the works of Tunisian scholars in Israel - Deshen, Shlomo (American Ethnologist, 1975)
Book publishing is an act of piety among the Tunisian immigrants of Israel. The literary content of books is less important than their talismanic value. The Tunisian community in Israel has abandoned many of its traditional religious practices, substituting for them pious acts such as pilgrimages and the publishing of religious books.
Keywords: Judaïsme – Djerba

Ethnicity and Citizenship in the Ritual of an Israeli Synagogue - Deshen, Shlomo (Southwestern Journal of Anthropology, 1972)
Tension between citizenship and ethnicity is expressed in an Israeli ethnic synagogue by changes in ritual and symbolism. The symbolic expression of these changes relates worshippers of the synagogue, who are recent immigrants to Israel, to their new heterogenous environment. Analysis of the changes in symbols demonstrates that the referential aspects have expanded, consistent with alterations in traditional relationships. The reinterpreted symbols may be categorized in terms of a typology of religious change as instances of "innovation," in the sense that the experiential range to which the symbol applies has been changed.
Keywords: Judaïsme – Djerba

An Outline of the Social Structure of the Jewish Communities in Djerba and Southern Tunisia from the End of the 19th Century until the 1950's / קווים למבנה החברתי של קהילות יהודי ג'רבה ודרום טוניסיה מסוף המאה היט עד לעליות ארצה - דשן, שלמה; Deshen, Shlomo (Zion / ציון, 1976)
Southern Tunisian Jewry has an uninterrupted and relatively peaceful history going back into antiquity. The general Berber population, particularly of the island of Djerba, has since the late 19th century developed a pattern of migrant merchants, who operate throughout Tunisia and retire in their old age to their homes. In this context, the Jews entered local commerce and filled the major local positions, however they did not engage in international or in itinerant commerce or trade. Djerban Jewry is therefore extremely sedentary and lacking in geographic mobility. As a consequence, the local community is relatively powerful over its individual members. Social control, particularly in religious matters, is strong because of the high visibility of individuals. Community organs are highly developed in comparison to other Jewish communities in North Africa. The continued development of community organs in the period under discussion is described in the paper on the basis of rabbinical treatises of recent generations.
Keywords: Judaïsme – Djerba

Towards a Description of the Traditional Pronunciation of the Jewish Community of Djerba / לתיאורה של מסורת ההגייה העברית של קהילת ג'רבה (תוניסיה) - Katz, Ktzia (Proceedings of the World Congress of Jewish Studies / דברי הקונגרס העולמי למדעי היהדות, 1973)
Keywords: Judaïsme – Djerba

The Varieties of Abandonment of Religious Symbols: Changes in Ethnic Synagogue / גוונים של נטישת סמלים דתיים: שינויים בבית כנסת עדתי - Deshen, Shlomo (Megamot, 1971)
Taking the Weberian use of the term "secularization" as a point of departure, the author questions a recent identification of the term with the abandonment of religious beliefs per se. He shows that an abandoning of religious beliefs, which can be effected either through the eradication or the effacement (terms he posits in his typology of religious changes) of religious symbols, is not necessarily an index of secularization. The two concepts in turn are demonstrated to be distinct phenomena growing out of very different sociological conditions and circumstances. Three cases of symbolic change which occurred in a Djerban synagogue in Israel are discussed and the analysis is extended through a comparison with an African ritual. The three Djerban examples in the Israeli environment and the African ritual were found to be instances of effacement. In all four cases the very act of abandonment of the religious symbols, which was due to the fact that the particular symbols in question no longer conforms with the experiential situation of the actors, led to a reaffirmation of the symbols.
Keywords: Judaïsme – Djerba

The Writing of Tunisian Sages in Israel / כתבי חכמי טוניסיה בישראל - Deshen, Shlomo; בוכריס, דוד; פרג'ון, פורטונה (Megamot, 1975)
This article deals with one aspect of the cultural and social problems encountered by Tunisian Jews in the course of their absorption in Israel. The article concentrates on the study of one of the outstanding occupations distinguishing the community — the publication of the works of Jewish sages, especially from Djerba Island. The publication of religious books, most of which are commentaries on the Bible and the Talmud, was a common phenomenon among the Jews of Djerba Island in particular. If the author of the work was dead, the publication of the work by the descendants raised the latter's social status since it proved that learning and wisdom were part of their family legacy. It also contained an element of honour for one's parents. After immigration to Israel another motive was added to the wish to publish the religious commentaries of a father or other relative — the desire to rescue these writings from oblivion in view of the decline of religious tradition and the secularization process among members of the Tunisian community The activity involved in publication among South Tunisian Jews is thus studied against the background of a rich religious-cultural tradition in which importance was attached to writing and publication and a present which is conceived as an age of decline and degeneration as far as religion is concerned. The amount of books published and circulated is relatively large considering the potential reader market — Jews who immigrated to Israel from South Tunisia. The findings reveal that the relatively wide circulation is not to be attributed to an improvement in their economic situation or the desire of people for prestige and social recognition. These factors explain only part of the phenomenon. A fuller explanation may be presented in symbolic and cultural terms. By engaging in publication or financing it, people express their respect for the deceased, especially if the authors are their ancestors. From this point of view, the content of the book is unimportant because the books as such has a religious value of its own and it is intended to express the loyalty of children to their fathers. This phenomenon may also be defined as the ritualization of literature. Another aspect of this ritualization is that a magical protective power is attached to the book i.e. the latter serve as amulets. This ritualization is apparently a substitute for the numerous specific religious acts many of which are no longer performed today. Instead of them, various activities to which a defusive religious value is attached, are now making their appearance.
Keywords: Judaïsme – Djerba

Ethnicity and Citizenship in the Ritual of a Synagogue of Tunisian Immigrants / עדתיות ואזרחות בבית-הכנסת של עולי טוניסיה בישראל - Deshen, Shlomo (Megamot, 1971)
The paper examines the nature of the changes in ritual that occurred in an Israeli ethnic synagogue and their symbolic expressions, particularly the tension between citizenship and ethnicity. Certain events taking place in, or concerning, a particular synagogue were studied. The symbolic expression of the changes was found to be a means of communion of the worshipper with his new heterogeneous environment. The symbolic reference was now wider and the symbolic changes implied a shift in a relationship formerly obtained. In order to analyse the symbolic changes more definitely, the author developed a typology of religious changes comprising several types of symbolic changes of which the examples in this paper fall into the category of "innovation."
Keywords: Judaïsme – Djerba